THE FATE OF THE IDEA OF PROGRESS IN THE DIGITAL AGE - Sukhova, Nadiia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Being at the stage of active socio-cultural restructuring, our civilization began to accumulate and develop its intellectual potential within digital technologies, creating a new logical and conceptual emergent digital system. The aim and tasks are the analysis of new conditions of human existence in digital reality, awareness of the limits of the implementation of new technologies, in particular, in education, medicine, and security. Research methods are analytical and descriptive methods, socio-cultural, general scientific principles of historicism, the unity of historical and logical, and a comparative approach. Research results. Today we need to reconsider the idea of progress, which contributed to the idea of a computer paradise on Earth. Christian Europe, the Muslims of the East, as well as Ancient Egypt, Mesopotamia, and the Roman Empire, had no idea of progress, but the idea of advancing to a certain end of history. The idea of progress today is reinforced by the idea of calculation and quantification using new digital technologies and the emergence of a new reality. The ambiguity of the digital age is that having great material opportunities, people are morally and spiritually devastated, enveloped in virtual and contrived practices aimed at education, medicine, security of human life in general. Discussion. Many thinkers (S. Pinker) try to prove the fruitfulness and usefulness of the idea of progress for the XXI century, forgetting about the mechanisms of gradual self-destruction. The Green Movement also has a quantitative dimension of progress that is absurd and detrimental to new strategies for human existence. Researchers (Sh. Amonoshvili, K. Salmivalli, O. Violet, V. Shatalov, etc.) emphasize that social networks, and rapid digitalization have irreversible effects on people’s thinking, feelings, and emotions, their communication, building society and political systems, etc. Conclusion. Experiencing the inevitable planetary changes, humanity must, above all, allow these processes to take place. Technocratic thinking is dangerous as a reference point for further development. The pursuit of quantitative indicators of progressive movement destroys the ethical and intellectual world of man because economic gain dominates over common sense. Awareness of the illusory nature of progress will allow humanity to really reconsider its values. Modern mass education with the sacralization of emptiness and meaninglessness of those values that cannot be stable tries to maintain the illusion of human superiority over nature. And does not mention the responsibility for human experiments in education and medicine.